Legal Protection For Juvenile Offenders In The Criminal Justice Process (Comparative Study Of Islamic Law And Positive Law In Indonesia) - Dudi Ruchendi (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2024)
This study aims to determine the rights of children who commit criminaloffenses in the judicial and investigative processes in legal protection. Themethod used is the normative juridical and sociological juridical approach. Theresults of this study are as follows: first, the investigation process at the Polres iscarried out by child investigators who are accompanied by parents/guardians,legal counsel, and Bapas. At the Polsek level, the investigation is carried out byinvestigators who usually conduct investigations on adults due to the need formore human resources. Legal counsel must accompany children who are stillsuspects. There is no intimidation during the investigation process; everythingis done according to the investigation procedure for children. Second, children’srights during the trial period are fulfilled and protected by judges and publicprosecutors by the Law on Juvenile Justice System. The rights contained inArticle 3 of Law No. 11/2012 have fully met the principles of legal protectionconsisting of 4 (four) principles: The child cannot fight alone, the best interestsof the child, the life cycle approach, and cross-sectoral.Keywords: Protection, law, juvenile offenses